EVOLUTION OF ISLAND ARCS AND GEODYNAMICS OF THE EASTERN CENTRAL ASIAN FOLDBELT IN THE NEOGEA - Zorin Y.A.; Sklyarov E.V.; Belichenko V.G.; Mazukabzov A.M. (My University, 2007)
The eastern part of the Central Asian foldbelt comprises the region located between the ancient Siberian and North China platforms. Some researchers believe that the Central Asian foldbelt is a collage of terranes formed in different geodynamic settings and that this foldbelt appeared after the opening of the Paleoasian ocean. Proponents of the concept of Altaides believe that all stratified rocks of the foldbelt are related to accretion–subduction wedges. However, proponents of both concepts admit the significant role of Riphean, Vendian–Lower Paleozoic, and middle Paleozoic island-arc formations in the foldbelt structure. These works paid little attention, however, to formations of back-arc (marginal) seas. The paleogeodynamic reconstructions proposed in them sometimes lack analogues in modern (Mesozoic–Cenozoic) plate tectonics. Taking into consideration recent data on the formation mechanism of island arcs and marginal seas, we propose in this communication a more rigorous and actualistic approach to paleogeodynamic reconstructions that can change (or specify) views on geodynamics of the eastern Central Asian foldbelt.